Genre Intersections and Transmediality in Mark Požlep’s Project Stranger than Paradise - Ana Gospić Županović ([sic])
The paper adopts a transmedial and multidisciplinary perspective to present and analyze the project Stranger than Paradise by Slovenian artist Mark Požlep, which ran from 2014 to 2016, covering the initial concept, its execution, and the subsequent presentations in various media: exhibitions and performances. The documentary material presented at the exhibition as a documentation of the original event is compared with the later performance of the same name with different collaborators working on the production. The paper focuses on the issue of hybrid genres in contemporary performance practices and examines how the performance of this play contributes to the modes and strategies of documentary theater, i.e., performance, while demonstrating that it can be placed in the context of post-documentary theater as it represents the so-called transition from directorial to authorial work. Keywords: musical performance, documentary performance, hybridization of genres, memory, ex-Yugoslavia